2011
DOI: 10.1021/la202201r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Thioether Spacer Containing Gemini Imidazolium Surfactants

Abstract: Twelve new gemini imidazolium surfactants have been synthesized, having dodecyl, tetradecyl, hexadecyl, and octadecyl chain lengths and three different spacers (i.e., -S-(CH(2))(n)-S-), where n = 2, 3, and 4 and their surface properties have been evaluated by surface tension and conductivity methods. The thermal degradation of these new gemini surfactants was determined by thermogravimetric analysis (TGA). These surfactants have low cmc values as compared to other categories of gemini cationic surfactants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 82 publications
5
105
0
1
Order By: Relevance
“…This may plausibly be due to: (a) protonated spacer will not bend (due to H-bonding) towards the core and not extend to the air as compared to polymethylene spacer and (b) at the interface, arrangement of amphiphile molecules may not be easy to adjust or giving a space to other amphiphiles with a bigger size protonated molecules in the spacer [50]. However, γ cmc increases and π cmc decreases with m which is in agreement with the earlier report [17,51]. Data revealed that the nature of the spacer can play a major role in the surface arrangements of the surfactant molecules.…”
Section: Surface Tension Measurementssupporting
confidence: 89%
See 1 more Smart Citation
“…This may plausibly be due to: (a) protonated spacer will not bend (due to H-bonding) towards the core and not extend to the air as compared to polymethylene spacer and (b) at the interface, arrangement of amphiphile molecules may not be easy to adjust or giving a space to other amphiphiles with a bigger size protonated molecules in the spacer [50]. However, γ cmc increases and π cmc decreases with m which is in agreement with the earlier report [17,51]. Data revealed that the nature of the spacer can play a major role in the surface arrangements of the surfactant molecules.…”
Section: Surface Tension Measurementssupporting
confidence: 89%
“…For conventional amphiphiles, n = 2 is used [1a]. In recent studies on geminis, the value of n was used either 2 or 3 [19,48,51]. It has been argued that with gemini surfactant ions and counter-ion are univalent, therefore, the value n = 2 should be used for calculating surface excess concentration.…”
Section: Surface Tension Measurementsmentioning
confidence: 99%
“…Gemini surfactants have attracted significant research efforts in the past couple of decades due to their enhanced properties (such as low CMC) compared to conventional single-chained amphiphils [1][2][3][4][5][6][7][8][9][10][11][12][13]. These are simply two charge centers (usually cationic), attached to hydrocarbon tails, and separated by a spacer: the sequence consists of a hydrocarbon tail, an ionic group, a spacer, an ionic group and a hydrocarbon tail [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The cmc's for the Geminis were much lower than the cmc's of the mono imidazolium surfactants. Gemini imidazolium-based surfactants and pyridinium-based surfactants with thioether spacers have very recently been described and characterized [41,42].…”
Section: Association Structuresmentioning
confidence: 99%